Compound haemangioma of lower lip: an interesting and rare case report - Chauhan, Devika; Hota, Subhransu Kumar; Kabra, Hardik; Giri, Ranjana; Senapati, Urmila; Tudu, Harish Chandra (International Journal of Contemporary Pediatrics, 2021)
Haemangiomas are common benign vascular tumours of infancy and childhood. Haemangiomas occur in 10-12% of children of 1 year of age and most of them are self-resolving within 9 years of age. Most common sites are head and neck (around 90%) and lip is one of the preferred sites. Sometimes persistence of haemangiomas may require surgical intervention. Capillary haemangiomas generally located superficially and cavernous haemangiomas located deep. Mixed capillary-cavernous haemangiomas or compound haemangiomas are one of the rarer types and location at lip rarest. Here we report a 14-years-old boy presented to paediatric surgery outdoor with swelling in lower lip for last 3 years. The excisional biopsy done with a clinical diagnosis of granuloma and sent for histopathological study. On microscopy of tissue sections given from lesion showed stratified squamous epithelium with sub epithelium revealing two distinct areas of capillary haemangioma component and cavernous haemangioma component within the lesion. So, final diagnosis of capillary-cavernous haemangioma (compound haemangioma) was made without any granuloma or malignant component. Patient followed up for six months and he was completely asymptomatic without any residual disease and recurrence.